2014
DOI: 10.1074/jbc.m113.525139
|View full text |Cite
|
Sign up to set email alerts
|

Primed Immune Responses to Gram-negative Peptidoglycans Confer Infection Resistance in Silkworms

Abstract: Background: Primed immune responses contribute to vertebrate host defense. Results: Silkworms acquire resistance to a pathogen by a preinjection of its heat-killed cells or its cell surface peptidoglycans. The amount of antimicrobial peptides is increased at the second round of infection. Conclusion: Invertebrates acquire infection resistance by peptidoglycan recognition and antimicrobial peptide increase. Significance: Molecular mechanisms of invertebrate primed immunity were revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Growing evidence suggests that a low dose of a pathogen may prime the immune response in insects, reducing the risk and severity of infection by the same pathogen later in life. Evidence for such priming‐induced immune protection has been reported in many insects including mealworm beetles (Daukšte, Kivleniece, Krama, Rantala, & Krams, ), bumble bees (Sadd & Schmid‐Hempel, ; Tidbury, Pedersen, & Boots, ), silkworms (Miyashita, Kizaki, Kawasaki, Sekimizu, & Kaito, ), fruit flies (Pham, Dionne, Shirasu‐Hiza, & Schneider, ), mosquitoes (Contreras‐Garduño, Rodríguez, Rodríguez, Alvarado‐Delgado, & Lanz‐Mendoza, ), and flour beetles (Roth, Sadd, Schmid‐Hempel, & Kurtz, ). Immune priming can also confer sustained protection via (i) ontogenic priming, where the benefit of priming can persist through metamorphosis (Moreno‐García, Vargas, Ramírez‐Bello, Hernández‐Martínez, & Lanz‐Mendoza, ; Thomas & Rudolf, ) and (ii) transgenerational immune priming, where the benefits are manifested in the next generation (Dubuffet et al., ; Moreau, Martinaud, Troussard, Zanchi, & Moret, ; Sadd & Schmid‐Hempel, ; Sadd & Schmid‐hempel, ; Zanchi, Troussard, Moreau, & Moret, ).…”
Section: Introductionmentioning
confidence: 96%
“…Growing evidence suggests that a low dose of a pathogen may prime the immune response in insects, reducing the risk and severity of infection by the same pathogen later in life. Evidence for such priming‐induced immune protection has been reported in many insects including mealworm beetles (Daukšte, Kivleniece, Krama, Rantala, & Krams, ), bumble bees (Sadd & Schmid‐Hempel, ; Tidbury, Pedersen, & Boots, ), silkworms (Miyashita, Kizaki, Kawasaki, Sekimizu, & Kaito, ), fruit flies (Pham, Dionne, Shirasu‐Hiza, & Schneider, ), mosquitoes (Contreras‐Garduño, Rodríguez, Rodríguez, Alvarado‐Delgado, & Lanz‐Mendoza, ), and flour beetles (Roth, Sadd, Schmid‐Hempel, & Kurtz, ). Immune priming can also confer sustained protection via (i) ontogenic priming, where the benefit of priming can persist through metamorphosis (Moreno‐García, Vargas, Ramírez‐Bello, Hernández‐Martínez, & Lanz‐Mendoza, ; Thomas & Rudolf, ) and (ii) transgenerational immune priming, where the benefits are manifested in the next generation (Dubuffet et al., ; Moreau, Martinaud, Troussard, Zanchi, & Moret, ; Sadd & Schmid‐Hempel, ; Sadd & Schmid‐hempel, ; Zanchi, Troussard, Moreau, & Moret, ).…”
Section: Introductionmentioning
confidence: 96%
“…I have previously reported that a pre-injection of heat-killed cells of Gram-negative bacteria, or its cell wall moiety (peptidoglycans), confers infection resistance to otherwise lethal bacterial infection in silkworm (Miyashita et al, 2014; Miyashita et al, 2015). Although the peptidoglycan-inducible immune priming conferred a full resistance to pathogenic Gram-negative bacteria, its proposed molecular mechanism (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although the peptidoglycan-inducible immune priming conferred a full resistance to pathogenic Gram-negative bacteria, its proposed molecular mechanism (i.e. antimicrobial peptide upregulation) takes long time to activate (Miyashita et al, 2014), which thus is not sufficient to suppress bacterial infection ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Insects, including silkworms, have innate immune systems conserved with mammals. In addition, silkworms have a primed immune system that has several characteristics that resemble acquired immune systems in vertebrates (24,25).…”
Section: Establishment Of Silkworm Infection Model For Human Pathogenmentioning
confidence: 99%